Specialised Vocabulary in Subtitling Science Documentaries - Vyzas, Theodoros (Journal of Audiovisual Translation, 2022)
This article describes an exploratory study which tries to shed light on audiovisual translation considered as specialised translation through two English language health-themed documentaries with Greek subtitles. The aim is to highlight the way English specialised vocabulary is translated into Greek. After a brief overview of the main aspects of interlingual subtitling and the general features of documentaries, the focus moves onto the translation of science documentaries as specialised texts. The methodology is based first on the formal characteristics of the specialised vocabulary identified, and second on a translation strategies model by means of which the translation of the specialised vocabulary is studied. The findings are discussed with emphasis on the specifics of the equivalences provided, in order to proceed to an overall account of the translation. Lay Summary Science documentaries make scientific subjects accessible to the general public. They popularise knowledge, so viewers can watch a film easy to understand. However, information on scientific matters is offered to the viewers mostly by means of specialised vocabulary. Things become more complicated when a documentary is on television in a country where people do not speak the language of the film. In such cases, subtitlers create subtitles used in order to make easier for local viewers to understand the scientific information presented in another language. Although subtitling is widespread all around the world, studies have only focused on subtitling in television series and cinema films. Moreover, researchers have shown little interest in translation of science documentaries from English into Greek. As my mother tongue is Greek, I wanted to study the way that the English specialised vocabulary in such films was translated into Greek. For this purpose, I studied all kinds of specialised words -medical, economic, legal and administrative terms- that were contained in two English-speaking documentaries investigating health issues. I must point out that subtitlers are hardly ever specialists in the scientific field of the documentaries they translate. By using a specific translation model, I found out that subtitlers had used various ways for the translation of English terms. What is interesting is that even when terms were translated into Greek by means of non-specialised words, the scientific content of both films was transferred into the subtitles, offering a readily comprehensible product without any loss of information.